A Superhydrophobic Sponge with Excellent Absorbency and Flame Retardancy1. (7th April 2014) - Ruan, Changping; Ai, Kelong; Li, Xingbo; Lu, Lehui
Abstract Frequent oil spillages and the industrial discharge of organic solvents have not only caused severe environmental and ecological damage, but also create a risk of fire and explosion. Therefore, it is imperative, but also challenging, to find high‐performance absorbent materials that are both effective and less flammable. Here we present a superior superhydrophobic sponge that exhibits excellent absorption performance through a combination of its superhydrophobicity, high porosity, and robust stability. More importantly, it inherits the intrinsic flame‐retardant nature of the raw melamine sponge, and is thus expected to reduce the risk of fire and explosion when being used as an absorbent for flammable oils and organic compounds. Moreover, the fabrication of this sponge is easy to scale up, since it does not use a complicated process or sophisticated equipment. These characteristics make the sponge a much more competitive product than the commercial absorbent, nonwoven polypropylene fabric.